2020
DOI: 10.1371/journal.pone.0238706
|View full text |Cite
|
Sign up to set email alerts
|

Morphological asymmetry, sex and dominant somatotype among Polish youth

Abstract: The aim of the present study was to determine the level of morphological asymmetry among the general population of Polish youth as it correlates to sex and body type. The anthropometric characteristics of a group of 618 Polish youths (354 males aged 19.5 ± 1.2 years and 264 females aged 19.2 ± 1.2 years) were evaluated to assess their somatotypes using the Heath-Carter method. Body composition was calculated using the bioelectrical impedance method, and the absolute asymmetry index was used for comparisons bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
1
2
0
1
Order By: Relevance
“…Males generally have more muscle mass and less body fat than females with HNC, even after accounting for differences in body size and weight. These findings are consistent with previous studies that have reported sex differences in body composition and metabolism [26][27][28]. Sex-specific reference values can aid in identifying individuals who are at a higher risk for health issues related to muscle mass and fat deposits, such as malnutrition and sarcopenia in patients with cancer.…”
Section: Discussionsupporting
confidence: 91%
“…Males generally have more muscle mass and less body fat than females with HNC, even after accounting for differences in body size and weight. These findings are consistent with previous studies that have reported sex differences in body composition and metabolism [26][27][28]. Sex-specific reference values can aid in identifying individuals who are at a higher risk for health issues related to muscle mass and fat deposits, such as malnutrition and sarcopenia in patients with cancer.…”
Section: Discussionsupporting
confidence: 91%
“…Luna-Villouta et al [ 35 ] also observed differences in BF and SMM percentages between a group of 58 male tennis players aged 15.4 ± 0.8 years and a group of 29 female tennis players aged 15.3 ± 0.8 years. These sex differences in body composition and somatotype were expected and have also been found between boys and girls of similar ages in other sports or in non-athlete populations [ 42 , 43 , 44 ].…”
Section: Discussionsupporting
confidence: 74%
“…The endomorph somatotype is dominant in the average woman, especially if she is not involved in sports while in men the mesomorph dominates. Many studies confirm that women are predominantly endomorphic with a secondary mesomorphic component [48][49][50]. 4).…”
Section: Weights and Biasesmentioning
confidence: 97%